On a functional equation that has the quadratic-multiplicative property - Park Choonkil; Tamilvanan Kandhasamy; Balasubramanian Ganapathy; Noori Batool; Najati Abbas (Open Mathematics, 2020)
In this article, we obtain the general solution and prove the Hyers-Ulam stability of the following quadratic-multiplicative functional equation:ϕ(st−uv)+ϕ(sv+tu)=[ϕ(s)+ϕ(u)][ϕ(t)+ϕ(v)]\phi (st-uv)+\phi (sv+tu)={[}\phi (s)+\phi (u)]{[}\phi (t)+\phi (v)]by using the direct method and the fixed point method.